Diabetes hos hund : utfodring, motion och vikt som möjliga predisponerande faktorer - Klinkenberg, Hanna (SLU/Dept. of Animal Environment and Health (until 231231), 2004)
This is a study of some risk factors for Diabetes Mellitus (DM) in dogs. As a pilot study it is meant to give information to be used in a planned later, larger and better controlled study. The present study hypothesized that suboptimal feeding (high percentage of homemade and table foods), lack of activity and overweight contribute to the risk of DM. Twenty consecutive dogs diagnosed with DM at the Veterinary University Clinic in Uppsala between 2000 – 2003 were chosen as the experimental group. A control group of 40 matched for age, breed and gender was recruited from the files of the Swedish Kennel Club. The owners received an inquiry with questions about feeding, activity and weight. A semi-structured telephone interview explored these variables in more detail.